Correction: Isoprene chain shuttling polymerisation between cis and trans regulating catalysts: straightforward access to a new material. Issue 46 (25th May 2017) - Phuphuak, Y.; Bonnet, F.; Stoclet, G.; Bria, M.; Zinck, P.
Abstract : Correction for 'Isoprene chain shuttling polymerisation between cis and trans regulating catalysts: straightforward access to a new material' by Y. Phuphuak et al., Chem. Commun., 2017, 53, 5330–5333.